Comments: Number of perceivable object color stimuli. Issue 5 (4th August 2016) - Kuehni, Rolf G.
Abstract : M. Brill, in his comments "Maximum number of discriminable colors in a region of uniform color space, " offers a different calculation method from that used by R. G. Kuehni in "How many object colors can we distinguish?, " one based on close‐packing of just noticeable difference spheres. The number per just noticeable difference (JND) sphere is lower than that derived in Kuehni's study. Based on the resulting number of close‐packed JND spheres in the CIECAM02/D65 object color solid and Brill's described multiplier of 5.923 potential stimuli within a JND sphere, the resulting number of distinguishable color stimuli is 9.114 million. © 2016 Wiley Periodicals, Inc. Col Res Appl, 00, 000–000, 2016